Universal human values is basis of interreligious dialogue (Journal of Philosophy Culture and Political Science, 2019)
This article considers interreligious dialogue and coordination of principles in interreligious to culture of the relations. And discusses the place of national clergy among national unity and religious uniqueness. Authors say that congress of leaders of world and traditional religions is the best way to show to the way population to unity, to the world. It was investigated that Kazakhstan society is tolerant to all world and traditional religious faiths and to their principles. Keywords:  secular, tolerance, spiritual culture, dialogue, traditional values, inter-religious harmony.